George Vancouver papers - Vancouver, George, 1757-1798.
Accounts (1793 March 8 and 1794 March 2) of Vancouver's voyage aboard the Discovery exploring the coastline of the Pacific Northwest and drafts (undated) of his poem, "Ko Lkonia."
Positive and negative photocopies.
British naval officer and explorer.
Collection material in English, with Hawaiian.
Forms part of: Library's Miscellaneous Manuscripts collection.
Keywords: Discovery (Ship : Launched 1789); Northwest, Pacific -- Discovery and exploration; Explorers; Naval officers, British